International health and spa tourists' motivational factors in Sabah, Malaysia: the push and pull factors / Inoormaziah Azman and Jennifer Kim Lian Chan - Azman, Inoormaziah; Kim, Jennifer Lian Chan (Universiti Teknologi MARA (UiTM), Malaysia, 2012)
Purpose: This qualitative study is attempted to provide an in-depth understanding of health and spa tourists' profiles and their key motivational factors of visiting health and spas at the resort hotels in Sabah, Malaysia by extending the push and pull motivational concept. Findings: Managerial Implications: The finding reveals that the health and spa tourists' motivations are mainly attributed to the push factors, which related to the psychological needs of the tourists including escape, rest and relaxation. The pull factors (health and spa attributes) mainly as the key attributes of the whole spa experiences, instead of the key attractiveness to the tourists to visit health and spa, which including professionalism, spa treatments and the physical looks of the spa establishment. It benefits the health and spa service providers in term of developing appropriate marketing strategies that concentrate on fulfilling the psychological needs of the tourists, and enhanced tourist satisfaction by paying attention to the key attributes that eventually contribute to a more remarkable spa experiences.